Advances and challenges of prenatal interventions for fetal tachyarrhythmias - Tang, Jiao; Huang, Pujue; Deng, Xue; Zhao, Lijuan; Zhai, Yang; Wang, Tao (Frontiers in Pediatrics, 2024)
It is estimated that 1%–2% of pregnancies are complicated by fetal arrhythmias, with most arrhythmias considered benign and not requiring further treatment or intervention. However, persistent tachyarrhythmias can lead to fetal heart failure, preterm birth, stillbirth, and increased risks during the perinatal period. Therefore, timely treatment during pregnancy is often necessary. Currently, prenatal treatment for fetal tachyarrhythmias (FTs) is primarily drug based, aiming to restore normal fetal heart rate, prevent or reverse fetal heart failure, and avoid adverse outcomes such as preterm birth and stillbirth. Despite decades of clinical experience, the lack of prospective, multicenter randomized clinical trials on the safety and efficacy of drugs means that there is still no universally accepted prenatal treatment regimen for FTs, and treatment relies on series of observational studies or clinical cases. Moreover, all drug treatments carry potential risks to the mother, fetus, and pregnancy, hence the need for more clinical diagnostic and therapeutic experience to provide more clinical evidence for prenatal treatment of FTs.